2020
DOI: 10.1007/s13353-020-00591-3
|View full text |Cite|
|
Sign up to set email alerts
|

Further phenotypic delineation of the auriculocondylar syndrome type 2 with literature review

Abstract: Auriculocondylar syndrome (ACS) is an ultra-rare disorder that arises from developmental defects of the first and second pharyngeal arches. Three subtypes of ACS have been described so far, i.e., ACS1 (MIM: 602483), ACS2 (MIM: 600810), and ACS3 (MIM: 131240). The majority of patients, however, are affected by ACS2, which results from the mutations in the PLCB4 gene. Herein, we have described an 8-year-old male patient presenting with ACS2 and summarized the molecular and phenotypic spectrum of the syndrome. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We note, however, that our patients did not have large, open fontanelles, the hallmark feature of trisomy 7p which has been linked to triple dosage of TWIST1 ,67 which may reflect having three copies of regulatory elements rather than three copies of the gene itself. Similarly, a significant number of DECIPHER duplications (~40%) at this locus were also associated with ARCND overlapping features, despite the variable phenotype and incomplete penetrance of ARCND 9 10 13 68. Interestingly, one of the duplications (276644) was entirely contained within the ARCND duplication, but this CNV did not span the known Twist1 regulatory element51 and the case was not associated with any features of ARCND.…”
Section: Discussionmentioning
confidence: 95%
“…We note, however, that our patients did not have large, open fontanelles, the hallmark feature of trisomy 7p which has been linked to triple dosage of TWIST1 ,67 which may reflect having three copies of regulatory elements rather than three copies of the gene itself. Similarly, a significant number of DECIPHER duplications (~40%) at this locus were also associated with ARCND overlapping features, despite the variable phenotype and incomplete penetrance of ARCND 9 10 13 68. Interestingly, one of the duplications (276644) was entirely contained within the ARCND duplication, but this CNV did not span the known Twist1 regulatory element51 and the case was not associated with any features of ARCND.…”
Section: Discussionmentioning
confidence: 95%
“…PLCB4 is a direct signaling effector of the endothelin receptor type A (EDNRA)‐Gq/11 pathway (Ellis et al., 1998 ; Gresset et al., 2012 ), which establishes the identity of neural crest cells (NCCs) that form lower jaw and middle ear structure and contributes to craniofacial development through induction, migration, and maintenance of NCCs (Bonano et al., 2008 ). Missense mutations of PLCB4 gene were predicted to act via a dominant‐negative mechanism to interfere in EDNRA signaling pathway (Bukowska‐Olech et al., 2021 ; Staus et al., 2016 ; Vegas et al., 2022 ). It was supported by the latest research which showed that PLCB4 gene variants interfere with EDNRA‐Gq/11‐mediated activity of wild‐type PLCB in a partially dominant‐negative manner, with this interference blocked by disrupting the Gq/11‐ PLCB 4 binding interface (Kanai et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reactions and PCR products purification were carried out following standard protocols, whereas specific primers were designed via the Primer3 tool v. 0.4.0. Next, Sanger sequencing was performed on an automated sequencer Applied Biosystems Prism 3700 DNA Analyzer using dye-terminator chemistry kit v.3, ABI 3130XL [ 26 ]. The analysis was performed applying the BioEdit tool and annotated against the GRCh38 human reference genome to map the deletion breakpoints or reference sequence NM_001164405.2 to analyze the BHLHA9 coding region.…”
Section: Methodsmentioning
confidence: 99%